LPTO-08. INTRATHECAL TRASTUZUMAB PLUS/MINUS IT TOPOTECAN FOR PATIENTS WITH HER2+ BREAST CANCER AND LEPTOMENINGEAL METASTASIS. (12th August 2019) - Trevino, Christopher R; Murthy, Rashmi K; Raghavendra, Akshara Singareeka; Loghin, Monica; Seligman, Christa; Ferguson, Sherise; Kamiya-Matsuoka, Carlos; Harrison, Rebecca; Sinicrope, Kaylyn D; Valero, Vicente; Tummala, Sudhakar; Hess, Kenneth; et al.
Abstract: BACKGROUND: Leptomeningeal metastasis (LM) is an aggressive complication of cancer. No standard therapies exist, although at our institution we commonly use IT topotecan in good-risk patients. We report our experience in patients with HER2+ breast cancer (BC) LM treated with intrathecal (IT) trastuzumab +/- IT topotecan. METHODS: We retrospectively reviewed records of patients managed with IT trastuzumab at MD Anderson Cancer Center from 2016–2019. Demographics, clinical course, and outcomes data (Kaplan-Meier) were collected and analyzed. RESULTS: 14 female patients (median age 49, range 33–67) with HER2+ BC (29% hormone receptor (HR) positive, 71% negative) were treated with IT trastuzumab (titrated to 40 mg -100 mg/week); 8 (57%) received concurrent IT topotecan. LM diagnosis was made in 64% by MRI alone, and 36% by both MRI and CSF cytology; 79% had brain metastases (BM), and of those, 55% (6/11) had active BM at LM diagnosis; 57% received WBRT prior to initiation of IT therapy. Median KPS was 90 (range, 60–100). Of those with initially positive cytology, 50% (4/8) converted to negative during treatment. MRI findings improved in 79%; 79% were symptomatic at diagnosis (most commonly ataxia, cranial neuropathy, headache); 70% (7/10) had symptom improvement on IT therapy. The only IT-associated symptom reported was mild nausea that occurred in 29%. Median time from diagnosis of metastatic BC was 10.7 mos. (range 0–83 mos); 36% had active extra-CNS disease and 86% received concurrent systemic therapy; 57% underwent change in systemic therapy during IT treatment; 91% were progression-free at 6 months, 32% at 24 months. Median overall survival from LM diagnosis was 24.7 months (95% CI 10.7, NR). CONCLUSIONS: IT trastuzumab is a safe and promising therapy for patients with HER2+ BC and LM. Dual IT therapy with trastuzumab and topotecan was well-tolerated and warrants further investigation in a larger study.